ETIKA GURU DALAM PERSPEKTIF ISLAM - Khuriah, Siti; Wardani, Siska Yuli; Khoiriah, Siti; Fatimah, Siti; Maemanah, Siti; Komalasari, Seri (STAI Darul Qalam Tangerang, 2025)
The teaching and learning process of a teacher is not only as a provider of knowledge that is transferred directly to students, so teachers must be creative and innovative in order to increase the motivation to teach and learn, the results of which can be applied in actions or behaviors that are in accordance with the Qur'an and Al-Hadith. In the concept of Islamic education, a teacher must have a controlled nature, spirit and strong determination. In order to be able to transform various developments in science that are in accordance with the Qur'an and Al-Hadith, so that what has been planned can complete the teaching and learning process on time. Teachers are not just unsung heroes, they have a very large active role in the formation of the personality of a generation, in their hands the country will be seen and the progress or decline of an education. A teacher must have knowledge to give to his students, besides that a teacher must have broad insight because in this way a teacher will be able to master his students properly, because in the Qur'an it is explained which means: